LEGAL ANALYSIS OF THE INHERITANCE RIGHTS OF CHILDREN BORN OUT OF WEDLOCK UNDER INDONESIA AND THAILAND LAW - Haura Kamila Zahra; Nursariani Simatupang (Pena Cendekia Insani, 2026)
Illegitimate children are a social phenomenon that still occurs frequently and raises legal issues, particularly regarding the civil status and inheritance rights of children. Differences in legal systems between countries lead to differences in the treatment of illegitimate children, especially in determining their legal relationship with their parents and inheritance rights. This study discusses the criteria and inheritance rights of illegitimate children according to Indonesian and Thai law through a comparative legal approach. In Indonesian law, the status of children born out of wedlock is determined by their birth outside of a legal marriage and initially only has a legal relationship with the mother, while the relationship with the biological father only arises after recognition or proof of blood relations (Article 43 of Law No. 1 of 1974, Civil Code, and Constitutional Court Decision No. 46/PUU-VIII/2010). Meanwhile, Thai law automatically recognizes children born out of wedlock as legitimate children of the mother (Section 1546 CCC), but legal relations with the father and inheritance rights only arise through strict legitimation (Sections 1547–1548 CCC). This study uses a normative legal research method with a legislative approach, literature review, and qualitative analysis. The results of the analysis show that the main difference between the two legal systems lies in the mechanisms of recognition and legitimation: Indonesia emphasizes proof of descent and recognition to obtain inheritance rights, while Thailand requires formal legitimation for children born out of wedlock to obtain status and inheritance rights equal to legitimate children. Although different, both legal systems seek to protect the inheritance rights of children born out of wedlock.